The Influence of the Romantic Genius in Early Christian Studies - Walsh, Robyn Faith (Relegere, 2015)
This article proposes that critical scholarship of the New Testament has inherited from German Romantic and Idealistic thought a number of presumptions about the role of the author that have contributed to idiosyncratic approaches to these texts when compared with allied studies of ancient literature. Namely, ``critical'' scholarship has continued to impose anachronistic, Romantic ideas of an implicit Volk (people, nation) or inspirational Geist (spirit) onto early literature about Jesus. I offer an alternative reading of the authorship of the gospels that reads them like other ancient literature, centered on concrete evidence for ancient literary practices.